2.6 Mb YAC contig of the human X inactivation center region in Xq13: physical linkage of the RPS4X, PHKA1, XIST and DXS128E genes. - Lafrenière, R; Brown, C; Rider, S; Chelly, J; Taillon-Miller, P; Chinault, A; Monaco, A; Willard, H (1993)
X chromosome inactivation is a mechanism of dosage compensation that regulates the expression of mammalian X-linked genes between XY males and XX females. This phenomenon is cis-acting, clonally heritable, and requires the presence of an X inactivation center (XIC). In our attempts to characterize this phenomenon, we have focused on the physical organization of the human XIC localized to Xq13. From previous studies, we had determined that the candidate XIC interval contained two loci (DXS128 and XIST) and was bound by the breakpoints of two structurally abnormal inactivated X chromosomes, a t(X;14) and an idic(Xp). Here we present a refined mapping of the XIC-containing region using the breakpoint of a late replicating rearranged X (rea(X)), and the initial characterization of a set of 40 yeast artificial chromosomes (YACs) derived from the XIC-containing region. These YACs form a 2.6 Mb contig which completely covers the XIC, and physically links the RPS4X, PHKA1, XIST, and DXS128E genes, as well as a laminin receptor pseudogene (LAMRP4). Furthermore, we have determined the relative orientations of these four genes, and have derived a restriction map of the region using the rare cutter enzymes BssHII, EagI, MluI, NruI, SalI, SfiI, SstII (or SacII), and NotI. We have identified at least 9 CpG-rich islands within this region, and have discovered a large (approximately 125 kb) inverted duplication proximal to the XIC based on symmetrical restriction patterns and homologous probes. We estimate the maximum size of the XIC-containing interval to be between 680 kb and 1200 kb, based on the localization of the breakpoints of the rearranged X chromosomes mentioned above. This lays the groundwork for the further characterization of the XIC region and the isolation of other expressed sequences therefrom.